2017
DOI: 10.2134/agronj2016.05.0256
|View full text |Cite
|
Sign up to set email alerts
|

Camelina Seed Yield and Fatty Acids as Influenced by Genotype and Environment

Abstract: Camelina (Camelina sativa L. Crantz) is an alternative oilseed crop with potential for fallow replacement in dryland cerealbased crop production systems in the semiarid Great Plains. Th e interaction between genotype and environment was investigated on camelina seed yield, oil content, and fatty acid composition across two locations in the U.S. Great Plains. Treatments were three spring camelina genotypes (cultivars Blaine Creek, Pronghorn, and Shoshone), three growing seasons (2013, 2014, and 2015) and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 45 publications
(87 reference statements)
9
23
0
Order By: Relevance
“…Obour et al (2017) also reported high protein and low oil content of camelina seeds associated with high air temperatures during flowering and seed fill. For instance, averaged across cultivars and seeding rates, protein content was greatest in 2016 (279 kg ha −1 ) and least in 2014 (257 kg ha −1 ), whereas oil content was least in 2016 (394 kg ha −1 ) and greatest in 2015 (407 kg ha −1 ).…”
Section: Seed Oil and Protein Content And Oil Yieldsupporting
confidence: 85%
See 4 more Smart Citations
“…Obour et al (2017) also reported high protein and low oil content of camelina seeds associated with high air temperatures during flowering and seed fill. For instance, averaged across cultivars and seeding rates, protein content was greatest in 2016 (279 kg ha −1 ) and least in 2014 (257 kg ha −1 ), whereas oil content was least in 2016 (394 kg ha −1 ) and greatest in 2015 (407 kg ha −1 ).…”
Section: Seed Oil and Protein Content And Oil Yieldsupporting
confidence: 85%
“…Seed crude protein contents of WG4 (279 g kg −1 ) and WG1 (277 g kg −1 ) were similar and significantly greater than those of Joelle (262 g kg −1 ) and Bison (263 g kg −1 ), which were not different from each other. An inverse relationship between seed oil and protein content has been reported by others for spring camelina (Sintim et al, 2016;Obour et al, 2017). Compared with the other cultivars, WG4 tended to have relatively high balance of protein and oil content.…”
Section: Seed Oil and Protein Content And Oil Yieldsupporting
confidence: 60%
See 3 more Smart Citations